PENDAMPINGAN PEMBELAJARAN SEBAGAI STRATEGI EDUKATIF DI KELURAHAN KEMANISAN SERANG - Rika Kartika; Gatot Hartoko; Fatari Fatari; Rahmawati Dewi; Suratmi Suratmi; Venty Ramadhanty (LPPM Universitas Bina Bangsa, 2023)
Quality human resources are born from education. Good edducation will produce good human resources as well. Based on the condition in the field, namely in Kemanisan Village, that elementary school age children, sepecially grade one, still really need assistance in learning, for example, there are children who are still not fluent in reading, so this community service activity is carried out to help elementary school age children in grade one, so they don’t get left behind in the development of the learning process. This community service approach is participatory action reseacrh. After carrying out this activity through evaluation, getting quite good result for the transfer knowladge given to this children. So that the community service activities carried out are beneficial and have a positive impact on children who need assistance in learning